A high coercivity neodymium cerium iron boron permanent magnet, its preparation method and application
By adjusting the substrate formulation and preparation method of neodymium cerium-ferrobor magnets, the formation of CeFe2 phase is suppressed and the distribution of RE-rich phases is optimized, and the low coercivity problem caused by CeFe2 phase in neodymium cerium-ferrobor magnets is solved, and a magnet with high coercivity and excellent magnetic properties is achieved.
Patent Information
- Application Number
- CN202111619345.1
- Authority / Receiving Office
- CN · China
- Patent Type
- Patents(China)
- Current Assignee / Owner
- Filing Date
- 2021-12-27
- Publication Date
- 2025-04-25
- Estimated Expiration
- 2041-12-27
AI Technical Summary
Among the existing neodymium cerium-ferrobor magnets, the existence of the CeFe2 phase makes it difficult for the magnet to obtain high coercive force, and the NdFe2 phase is difficult to form, affecting magnetic properties.
By adjusting the substrate formulation and preparation method of neodymium cerium-ferroboron magnet, the formation of CeFe2 phase is suppressed, the distribution of RE-rich phase is optimized, and the distribution is uniformly and finely at the grain boundary is reduced, thereby reducing the area ratio of the clumped RE-rich phase.
The high coercive force and excellent magnetic properties of neodymium cerium-ferrobor magnets are achieved. By suppressing the CeFe2 phase and optimizing the distribution of RE-rich phases, the nucleation and expansion of the reverse magnetization domain are reduced, and the residual magnetic induction strength of the magnet is improved.
Smart Images

Figure CN114284019B_ABST
Abstract
Description
Technical Field
[0001] The invention belongs to the field of rare earth permanent magnets, and in particular relates to a high coercive force Nd:Ce:Fe:B permanent magnet and a preparation method and application thereof. Background Art
[0002] As the third generation of rare earth permanent magnet materials, sintered NdFeB is mainly composed of rare earth PrNd, iron, boron and other elements. Due to its excellent magnetic properties and high cost performance, it is widely used in various rare earth permanent magnet motors, smart consumer electronics, medical devices and other fields. With the rapid development of low-carbon environmental protection economy and high-tech, the demand for sintered NdFeB magnets is growing, which has greatly driven the consumption of rare earth PrNd resources and caused the price of PrNd to gradually increase. Ce, as a rare earth element with similar chemical properties to PrNd and the most abundant reserves, is used in sintered NdFeB to replace Pr and Nd, which can not only reduce the cost of raw materials, but also help to achieve the balanced utilization of rare earth resources.
[0003] However, due to the mixed valence characteristics of Ce, Ce with a smaller ionic radius tends to form CeFe2 phase, which tends to exist in the form of separate grains in the magnet, resulting in a lack of RE-rich phase distributed along the grain boundaries between the main phase grains. The reverse magnetization domain is easy to nucleate and expand, and it is difficult for the magnet to obtain high coercive force. At the same time, the magnetic exchange coupling effect generated by the direct contact between adjacent main phase grains also significantly reduces the residual magnetic induction intensity of the magnet. The NdFe2 phase is difficult to form in the magnet. Therefore, in order to achieve the preparation of high-performance Ce-rich NdCeFeB magnets, suppressing the existence of CeFe2 phase in the form of grains and optimizing the distribution of RE-rich phase in NdCeFeB magnets have become technical problems that need to be solved urgently. Summary of the invention
[0004] In order to improve the above technical problems, the present invention provides a NdCeFeB permanent magnet, wherein the NdCeFeB permanent magnet has at least one of the following characteristics:
[0005] The area of RE-rich phase at the grain boundaries in the magnet accounts for more than 4% of the entire field of view;
[0006] The RE-rich phase at the grain boundaries in the magnet is evenly and finely distributed;
[0007] The average value of the ratio of the area of the agglomerated grain boundary RE-rich phase located at the intersection of three or more main phase grains to the total area of all three or more adjacent main phase grains is ≤30%.
[0008] According to the embodiment of the present invention, the distribution of the agglomerated grain boundary RE-rich phase at the intersection of three or more main phase grains and all three or more adjacent main phase grains around is basically as follows: Figure 3 shown.
[0009] According to an embodiment of the present invention, the RE includes neodymium (Nd) and may also include at least one selected from the following rare earth elements: cerium (Ce), lanthanum (La), praseodymium (Pr), yttrium (Y), gadolinium (Gd), terbium (Tb), dysprosium (Dy) and holmium (Ho), etc.
[0010] According to an embodiment of the present invention, the area of the RE-rich phase at the grain boundary in the magnet occupies more than 6% of the entire field of view area.
[0011] According to an embodiment of the present invention, the average ratio of the area of the agglomerated grain boundary RE-rich phase located at the intersection of three or more main phase grains to the total area of all three or more adjacent main phase grains is ≤15%, more preferably ≤10%, and more preferably ≤7%.
[0012] In the present invention, the vertical orientation surface of the Nd:Ce:Fe:B permanent magnet is polished and tested by using a field emission electron probe microanalyzer (FE-EPMA) (JEOL, 8530F), and the area ratio is analyzed by using Image-Pro Plus software.
[0013] In the present invention, the field of view area refers to the image display range detected by FE-EPMA or SEM, and there is no requirement for the magnification ratio of the test sample image, which is exemplarily magnified by 200, 500, 800, 1000 or 1500 times.
[0014] In the present invention, the adjacent main phase grains refer to the main phase grains adjacent to the grain boundary RE-rich phase.
[0015] According to an embodiment of the present invention, the main phase has R2Fe 14 B structure.
[0016] According to an embodiment of the present invention, the average grain size of the main phase grains of the NdCeFeB permanent magnet is 5-10 μm.
[0017] According to an embodiment of the present invention, the Nd:Ce:Fe:B permanent magnet has the following chemical formula: a RH b RL 1-a-b ) x Fe 100-x-y-z TM y B z ;
[0018] Among them: 20≤x≤40, 0.5≤y≤10, 0.9≤z≤1.5, 0.05≤a≤0.65, 0≤b≤0.25; the RH element is at least one of Dy, Tb, Ho, and Gd, the RL element is selected from at least one of Pr, Nd, La, and Y, and contains at least Nd; the TM element is at least one of Co, Cu, Ga, Al, Zr, and Ti.
[0019] According to an embodiment of the present invention, the RH element is preferably Dy.
[0020] According to an embodiment of the present invention, the RL element is preferably Pr or Nd.
[0021] According to an embodiment of the present invention, the TM elements are a mixture of Co, Cu, Ga, Al, Zr and Ti.
[0022] According to an embodiment of the present invention, 25≤x≤35, 1≤y≤5, 0.9≤z≤1.3, 0.05≤a≤0.25, and 0.01≤b≤0.1.
[0023] The present invention also provides a method for preparing the above-mentioned NdCeFeB permanent magnet, wherein the method comprises powdering, pressing, sintering and aging treatment of raw materials including Ce element, RL element, Fe element, TM element, B element and optionally RH element, to prepare the NdCeFeB permanent magnet;
[0024] Among them, RL element, TM element and RH element have the above meanings.
[0025] According to an embodiment of the present invention, the method comprises preparing the Nd:Ce:Fe:B permanent magnet by powdering, pressing and sintering raw materials including Ce, RL, Fe, TM, B and RH.
[0026] According to the embodiment of the present invention, the addition amount of each raw material is as follows (Ce a RH b RL 1-a-b ) x Fe 100-x-y-z TM y B z Add in stoichiometric ratio.
[0027] According to an embodiment of the present invention, a lubricant may be added during the preparation of the permanent magnet, and the lubricant is selected from one or more of calcium stearate, zinc stearate, tributyl borate, isopropyl alcohol, petroleum ether, etc. Preferably, the amount of the lubricant may be 0.01-2wt% of the total weight of the powder, exemplified by 0.01wt%, 0.05wt%, 0.1wt%, 0.5wt%, 1wt%, 2wt%.
[0028] According to an embodiment of the present invention, the method comprises: first preparing raw materials including Ce elements, RL elements, Fe elements, TM elements, B elements, and RH elements into alloy flakes, then subjecting the alloy flakes to hydrogen crushing, dehydrogenation, and grinding to prepare alloy powder, and then performing pressing, sintering, and aging treatment to prepare the Nd:CeFeB permanent magnet.
[0029] According to an embodiment of the present invention, the method may further include: (K1) firstly preparing Ce-free main phase alloy flakes and Ce-containing auxiliary phase alloy flakes respectively;
[0030] The Ce-free main phase alloy flakes are prepared by smelting and condensing raw materials of RL element, Fe element, TM element and B element, and optionally existing or not existing RH element;
[0031] The Ce-containing auxiliary phase alloy flakes are prepared by smelting and condensing raw materials of Ce element, RL element, Fe element, TM element and B element, and optionally existing or not existing RH element;
[0032] (K2) The Ce-free main phase alloy flakes and Ce-containing auxiliary phase alloy flakes in step (K1) are respectively subjected to hydrogen crushing, dehydrogenation, and air flow grinding to form alloy powders; a lubricant is optionally added, and the powders are pressed, sintered, and aged to prepare the Nd:Ce:Fe:B permanent magnets.
[0033] According to an embodiment of the present invention, the method may further include: (K1) firstly preparing Ce-free main phase alloy flakes and Ce-containing auxiliary phase alloy flakes respectively;
[0034] The Ce-free main phase alloy flakes are prepared by melting and condensing raw materials of RL element, RH element, Fe element, TM element and B element to form alloy flakes;
[0035] The Ce-containing auxiliary phase alloy flakes are prepared by melting and condensing raw materials of Ce element, RL element, RH element, Fe element, TM element and B element to form alloy flakes;
[0036] (K2) The Ce-free main phase alloy flakes and Ce-containing auxiliary phase alloy flakes in step (K1) are respectively subjected to hydrogen crushing, dehydrogenation, and air flow grinding to form alloy powders; a lubricant is optionally added, and the powders are pressed, sintered, and aged to prepare the Nd:Ce:Fe:B permanent magnets.
[0037] According to an embodiment of the present invention, in step (K2), the Ce-free main phase alloy flakes and Ce-containing auxiliary phase alloy flakes in step (K1) are hydrogen crushed, dehydrogenated, and air flow ground into alloy powder; and a lubricant is added, pressed, and sintered to prepare the Nd:Ce:Fe:B permanent magnet.
[0038] According to an embodiment of the present invention, the method may further include: (S1) first preparing Ce-free main phase alloy flakes and Ce-containing auxiliary phase alloy flakes respectively, and respectively preparing main phase alloy powder and auxiliary phase alloy powder by hydrogen crushing, dehydrogenation and air flow grinding;
[0039] The Ce-free main phase alloy flakes and Ce-containing auxiliary phase alloy flakes have the above meanings;
[0040] (S2) mixing the main phase alloy powder and the auxiliary phase alloy powder in step (S1), optionally adding or not adding a lubricant, pressing, sintering, and aging treatment to prepare the Nd:Ce:Fe:B permanent magnet.
[0041] According to an embodiment of the present invention, in step (S2), the main phase alloy powder and the auxiliary phase alloy powder in step (S1) are mixed, and a lubricant is added, and the mixture is pressed, sintered, and aged to prepare the Nd:Ce:Fe:B permanent magnet.
[0042] According to an embodiment of the present invention, in step (S2), the mass ratio of the main phase alloy powder to the auxiliary phase alloy powder is (1-40):1, exemplified by: 2.7:1, 10:1.
[0043] According to an embodiment of the present invention, the thickness of the alloy flakes (including main phase alloy flakes and auxiliary phase alloy flakes) is 0.1-0.4 mm, exemplified by 0.1 mm, 0.2 mm, 0.25 mm, 0.3 mm, and 0.4 mm.
[0044] According to an embodiment of the present invention, the alloy flakes (including main phase alloy flakes and auxiliary phase alloy flakes) are made by vacuum melting various raw materials and then casting. Exemplarily, the melting of the alloy flakes is carried out in a vacuum induction furnace.
[0045] Preferably, the smelting is performed under an inert atmosphere, for example, under a nitrogen or argon atmosphere, preferably under an argon atmosphere.
[0046] Preferably, the casting temperature of the alloy flake smelting process is 1300-1500°C, exemplarily 1300°C, 1400°C, 1500°C.
[0047] Preferably, the casting process of the alloy flakes is to cast the molten raw material liquid onto a rotating water-cooled copper roller. Further, the rotating speed of the rotating water-cooled copper roller is 15-45rpm, exemplified by 15rpm, 20rpm, 25rpm, 30rpm, 40rpm, 45rpm.
[0048] Preferably, the average particle size of the alloy powder (including the main phase alloy powder and the auxiliary phase alloy powder) is 2-6 μm, exemplarily 2 μm, 3 μm, 3.5 μm, 4 μm, 5 μm, 6 μm. Exemplarily, the average particle size of the main phase alloy powder is 4-6 μm; the average particle size of the auxiliary phase alloy powder is 3-5 μm.
[0049] According to an embodiment of the present invention, the preparation method further comprises pressing the alloy powder into a compact.
[0050] According to an embodiment of the present invention, the compression molding includes orientation compression molding and isostatic pressing molding. Preferably, the green compact is firstly obtained by orientation compression molding and then by isostatic pressing molding to improve the density of the green compact. Further, the orientation pressing is performed in a magnetic field, and the isostatic pressing is performed in an isostatic press.
[0051] Preferably, the mixed powder is subjected to orientation pressing and molding under the protection of an inert atmosphere, for example, under a nitrogen or argon atmosphere, preferably under a nitrogen atmosphere.
[0052] Preferably, the magnetic field strength of the orientation magnetic field is 2-5T, exemplified by 2T, 3T, 4T, and 5T.
[0053] Preferably, the isostatic pressing pressure is 150-260 MPa, exemplified by 150 MPa, 180 MPa, 185 MPa, 200 MPa, 220 MPa, 240 MPa, and 260 MPa.
[0054] Preferably, the density of the compact is 4-6 g / cm 3 , exemplified by 4 g / cm 3 , 4.2g / cm 3 4.6g / cm 3 , 5g / cm 3 , 6g / cm 3 .
[0055] According to an embodiment of the present invention, before the sintering treatment, the green compact is also subjected to a heat treatment, the heat treatment temperature is 100-950°C, preferably 150-900°C, the heat treatment holding time is 60-120min, and illustratively, the heat treatment temperature is 3-6 stages, the heat holding temperature of each stage of the heat treatment can be the same or different, the heat holding time can be the same or different, and the heat treatment stage can be carried out under an inert gas or under a vacuum state. Exemplarily, the heat treatment temperature is 4 stages, which are 100-200°C, 200-550°C, 550-700°C, and 700-950°C, respectively.
[0056] According to an embodiment of the present invention, the sintering is vacuum liquid phase sintering, which has more than four sintering and heat preservation stages, for example, 4-10 sintering and heat preservation stages, the temperature of the sintering and heat preservation stages is 900-1150°C, preferably 950-1100°C, exemplified by 900°C, 950°C, 1000°C, 1010°C, 1015°C, 1030°C, 1040°C, 1050°C, 1070°C, 1100°C, and the heat preservation temperatures of multiple heat preservation stages can be the same or different. The heat preservation time is 40-140min, preferably 50-100min, exemplified by 40min, 50min, 60min, 70min, 80min, 90min, 110min, and the heat preservation time can be the same or different. The sintering and heat preservation stage can be carried out under an inert gas or under a vacuum state.
[0057] Preferably, the sintering and heat-insulating stage includes a heating stage, and the heating rate of the heating stage is 0.5-5°C / min, more preferably 1-4°C / min; the heating rate of each heating stage can be the same or different.
[0058] According to the implementation scheme of the present invention, between each two adjacent sintering and heat preservation processes, the next heating and heat preservation process can be directly carried out after the previous sintering and heat preservation stage is completed, or after the previous sintering and heat preservation stage is completed, cooling is first carried out, and then the next heating and heat preservation process is carried out. The cooling temperature is not limited, and it can be lower than the temperature of the previous sintering and heat preservation stage. There is no special limit on the number of cooling stages, as long as the required cooling temperature is reached; that is, between each two adjacent sintering and heat preservation processes, the process can be any random. For example, after the previous sintering and heat preservation stage is completed, 1-10 stages of cooling are carried out first, and then the next heating and heat preservation process is carried out. The temperatures of 1-10 cooling stages can be the same or different. For example, after the insulation is completed, the cooling temperature is 500-1050℃.
[0059] According to an embodiment of the present invention, the aging treatment is performed after the sintering treatment is cooled. Exemplarily, the aging treatment includes: after the sintering is completed, cooling to room temperature, and then heating treatment.
[0060] Preferably, the aging treatment is a secondary aging treatment, comprising: heating for a first aging treatment, the first aging treatment temperature is 800-950°C, and the insulation time is 160-300min; cooling to below 210°C, and then heating for a second aging treatment, the second aging treatment temperature is between 450-600°C, and the insulation time is 240-360min.
[0061] According to an embodiment of the present invention, the method for preparing the NdCeFeB permanent magnet comprises the following steps:
[0062] Step 1: According to (Ce a RH b RL 1-a-b ) x Fe 100-x-y-z TM y B z Composition and proportion: The ingredients are weighed and mixed, and smelted in a vacuum induction furnace under the protection of Ar gas atmosphere. The molten melt is cast onto a rotating quenching roller, and then thrown onto a cooling plate for cooling to prepare alloy flakes.
[0063] Step 2, preparing alloy powder by subjecting the alloy flakes to hydrogen crushing, dehydrogenation and air flow milling treatment;
[0064] Step 3, orienting and pressing the alloy powder in a magnetic field to obtain a green compact, and pressing the green compact by an isostatic press to further increase the density of the green compact;
[0065] Step 4: sintering the compact in a sintering furnace with N sintering and heat preservation stages, and performing aging treatment to prepare NdCeFeB permanent magnets, 4≤N≤10.
[0066] According to an embodiment of the present invention, the method further comprises a grain boundary diffusion treatment step, wherein the surface of the NdCeFeB permanent magnet prepared after sintering is ground, coated with a heavy rare earth diffusion source, and subjected to diffusion treatment to prepare a grain boundary diffused NdCeFeB permanent magnet.
[0067] Preferably, the diffusion treatment includes applying diffusion material to the surface of the magnet, performing vacuum heating diffusion treatment, diffusion cooling and diffusion aging treatment.
[0068] According to an embodiment of the present invention, one or more pure metals, alloys, compounds, etc. of heavy rare earth RH (Dy, Tb) can be attached to the surface of the NdCeFeB permanent magnet by spraying, examples of which are: at least one of pure metals of Dy and / or Tb, hydrides of Dy and / or Tb, oxides of Dy and / or Tb, hydroxides of Dy and / or Tb, fluorides of Dy and / or Tb, etc.; exemplified by dysprosium fluoride.
[0069] According to an embodiment of the present invention, the diffusion treatment may be performed in a vacuum heat treatment furnace.
[0070] Preferably, the temperature of the vacuum heating diffusion treatment is 800-980° C., and the time of the vacuum heating diffusion treatment is 5-45 hours.
[0071] Preferably, the temperature of the diffusion cooling is below 100°C.
[0072] Preferably, the temperature of the diffusion aging treatment is 420-650° C., for example, 550° C., and the time of the diffusion aging treatment is 3-10 h.
[0073] According to an embodiment of the present invention, after the sintering process and before the diffusion treatment, the green body may be processed into a target size.
[0074] The present invention also provides applications of the Nd:Ce:Fe:B permanent magnet in the fields of rare earth permanent magnet motors, smart consumer electronic products, medical equipment, etc.
[0075] Beneficial effects of the present invention:
[0076] The present invention reduces the moving distance of the solid-liquid interface on the surface of the main phase grain of NdCeFeB to the solid phase by adjusting the base material formula, preparation method and sintering system of NdCeFeB, slows down the melting of the main phase grains, inhibits the growth of the main phase grains, and enhances the capillary force of the grain boundary, so that the molten RE-rich phase is distributed along the grain boundary, and the proportion of the area of the agglomerated grain boundary RE-rich phase located at the intersection of more than three main phase grains to the total area of all more than three adjacent grains around is reduced, so that the area ratio of the RE-rich phase in the magnet to the entire field of view is reduced and is evenly and finely distributed. At the same time, a continuous and smooth thin layer of grain boundary RE-rich phase is formed to divide and surround the main phase grains, repair the grain boundary defects, thereby inhibiting the nucleation of the reverse magnetization domain, hindering the movement of the reverse magnetization domain wall, and effectively isolating the magnetic exchange coupling between the main phase grains, so that the permanent magnet has higher magnetic properties.
[0077] The addition of Ce will change the composition and structural morphology of the grain boundary phase in the magnet, reduce the melting point of the RE-rich phase, reduce the sintering and aging temperature of the magnet, and make the grain boundary RE-rich phase tend to be distributed in agglomerates. As the Ce content increases, the tendency of the grain boundary phase to be distributed in agglomerates becomes more significant, which will increase the grain boundary defects and the main phase grains will contact each other, thereby reducing the magnetic properties. Therefore, the present invention further extends the sintering cycle, increases the holding time, promotes the distribution of the molten RE-rich phase along the main phase grains, increases the ratio of the two-particle grain boundary RE-rich phase, makes it evenly and finely distributed in the magnet, reduces defects and inhibits the nucleation of the reverse magnetization domain, and achieves the purpose of optimizing the magnet microstructure and magnetic properties.
[0078] In addition, the magnet prepared by the present invention has an excellent diffusion effect when used as a grain boundary diffusion magnet substrate. Since the RE-rich phase in the magnet is continuously distributed along the grain boundary, more channels are provided for diffusion, which helps to increase the diffusion depth of the diffusion source into the magnet, helps to improve the distribution uniformity of the diffusion source in the magnet, and helps to improve the consistency of the internal organizational components of the diffusion magnet, thereby further improving the magnetic properties of the diffusion magnet. BRIEF DESCRIPTION OF THE DRAWINGS
[0079] Figure 1 This is a scanning electron microscope image of the grain boundary phase and main phase in the magnet in Comparative Example 2.
[0080] Figure 2This is a scanning electron microscope image of the grain boundary phase and the main phase in the magnet in Example 1.
[0081] Figure 3 It is a distribution diagram of the agglomerated grain boundary RE-rich phase at the intersection of three or more main phase grains of the present invention and all the surrounding three or more main phase adjacent grains. DETAILED DESCRIPTION
[0082] The technical scheme of the present invention will be further described in detail below in conjunction with specific embodiments. It should be understood that the following embodiments are only exemplary descriptions and explanations of the present invention and should not be construed as limiting the scope of protection of the present invention. All technologies implemented based on the above content of the present invention are included in the scope that the present invention is intended to protect.
[0083] Unless otherwise specified, the raw materials and reagents used in the following examples are commercially available or can be prepared by known methods.
[0084] In the following examples of the present invention, PrNd is added in the form of an alloy, the other metals are added in the form of simple substances, and B is provided by B-Fe sand.
[0085] Example 1
[0086] (1) According to the designed proportion of 100 mass% of the components: PrNd: 29wt.%, Ce: 3.7wt.%, Dy: 0.4wt.%, Co: 1.2wt.%, Cu: 0.3wt.%, Ga: 0.1wt.%, Al: 0.53wt.%, Zr: 0.12wt.%, Ti: 0.12wt.%, B: 0.99wt.%, Fe balance, weigh the raw materials, use a vacuum induction melting furnace to melt under the protection of Ar gas atmosphere, cast the molten liquid onto a quenching roller with a rotation speed of 32rpm, the liquid casting temperature is 1400℃, and the alloy flakes with an average thickness of 0.25mm are obtained;
[0087] (2) The alloy flakes are subjected to hydrogen crushing, dehydrogenation, and air flow grinding to form alloy powder with an average particle size of 3.7 μm, and a lubricant zinc stearate accounting for 0.05 wt% of the weight of the alloy powder is added under N2 atmosphere protection, and the mixture is stirred and mixed evenly;
[0088] (3) Under the protection of N2 atmosphere, the mixed powder in step (2) was filled into the mold cavity of the pressing equipment mold, and the oriented magnetic field strength was 3T for oriented molding, and then the isostatic pressing was performed in an isostatic press at a pressure of 185 MPa and a holding pressure of 8 s to obtain a density of 4.2 g / cm 3 of compact;
[0089] (4) The green body is placed in a sintering furnace and subjected to a heating treatment in a vacuum atmosphere. The green body is kept at 150°C and 260°C for 100 min respectively for lubricant removal treatment, and kept at 600°C and 900°C for 90 min respectively for degassing treatment. Then, a 4-stage sintering and heat-insulating process is performed. After each sintering and heat-insulating stage is completed, the temperature is first lowered to 1000°C and then raised to the next heating step. The specific sintering process is shown in Table 1. After the fourth stage of sintering and heat-insulating is completed, the green body is directly cooled to room temperature to obtain a sintered body.
[0090] (5) Aging treatment: Take the above sintered body, heat it to 900°C and keep it for 180 minutes, then cool it to 200°C, then heat it to 530°C and keep it for 240 minutes, and then cool it to room temperature to obtain a magnet after aging treatment. The NdCeFeB permanent magnet has the following chemical formula: (Ce 0.11 RH 0.01 RL 0.88 ) 33.1 Fe 63.56 TM 2.35 B 0.99 ;
[0091] The RH elements are Dy, the RL elements are Pr and Nd; and the TM elements are Co, Cu, Ga, Al, Zr and Ti.
[0092] Figure 2 The scanning electron microscope images of the grain boundary phase and the main phase in the magnet in Example 1 are shown in FIG. Figure 2 It can be seen that the RE-rich phase is evenly distributed and fine.
[0093] Example 2
[0094] Example 2 uses the same formulation, smelting, powder making, pressing, and aging processes as Example 1, with the only difference being that a 5-stage sintering and heat-insulating process is used. The specific sintering process is shown in Table 1.
[0095] Comparative Example 1
[0096] The difference between Comparative Example 1 and Example 1 is only in the sintering process. The temperature is raised according to the conventional sintering process and a heat preservation sintering treatment is performed. The specific sintering process is shown in Table 1.
[0097] Comparative Example 2
[0098] The difference between Comparative Example 2 and Example 1 is that Comparative Example 2 adopts a three-stage sintering and heat preservation process, and after each sintering and heat preservation stage, the temperature is first lowered to 1000°C and then raised to the next heating process. The specific sintering process is shown in Table 1.
[0099] Comparative Example 3
[0100] Comparative Example 3 is different from Example 1 only in that: according to the composition design ratio: PrNd: 32.2wt.%, Ce: 0.5wt.%, Dy: 0.4wt.%, Co: 1.2wt.%, Cu: 0.3wt.%, Ga: 0.1wt.%, Al: 0.53%, Zr: 0.12wt.%, Ti: 0.12wt.%, B: 0.99wt.%, Fe balance. The preparation method is exactly the same as that of Example 1, and the Nd-Ce-Fe-B permanent magnet has the following chemical formula: (Ce 0.02 RH 0.01 RL 0.97 ) 33.1 Fe 63.56 TM 2.35 B 0.99 ;
[0101] The RH elements are Dy, the RL elements are Pr and Nd; and the TM elements are Co, Cu, Ga, Al, Zr and Ti.
[0102] Figure 1 The scanning electron microscope images of the grain boundary phase and the main phase in the magnet in Comparative Example 2 are shown in FIG. Figure 1 It can be seen that the RE-rich phase is coarse and unevenly distributed.
[0103] Comparative Example 4
[0104] The difference between Comparative Example 4 and Comparative Example 3 is that a three-stage sintering and heat preservation process is adopted. The specific sintering process is shown in Table 1.
[0105] Table 1 Specific sintering process parameters of Examples 1-2 and Comparative Examples 1-4
[0106]
[0107]
[0108] Table 1 (Continued) Specific sintering process parameters of Examples 1-2 and Comparative Examples 1-4
[0109]
[0110] Example 3
[0111] Example 3 The magnet after sintering and aging in Example 1 was processed into a thin sheet product with a length of 20 mm, a width of 20 mm, and a thickness of 5 mm. A 1 mm thick dysprosium fluoride film was applied on the surface of the magnet by a dipping process, and then the diffusion treatment was carried out at 900°C for 15 hours. After the diffusion temperature was cooled to below 100°C, the temperature was raised to 550°C for 5 hours of aging treatment to prepare a grain boundary diffused NdCeFeB permanent magnet. The final magnet was subjected to magnetic property testing.
[0112] Comparative Example 5
[0113] Example 5 The magnet after sintering and aging in Comparative Example 2 was processed into a thin sheet product with a length of 20 mm, a width of 20 mm, and a thickness of 5 mm. A 1 mm thick dysprosium fluoride film was applied on the surface of the magnet by a dipping process, and then the diffusion treatment was carried out at 900°C for 15 hours. After the diffusion temperature was cooled to below 100°C, the temperature was raised to 550°C for 5 hours of aging treatment to prepare a grain boundary diffused NdCeFeB permanent magnet. The final magnet was subjected to magnetic property testing.
[0114] Example 4
[0115] (1) According to the designed proportion of 100 mass % of the components: PrNd: 32.6wt.%, Dy: 0.4wt.%, Co: 1.3wt.%, Cu: 0.38wt.%, Ga: 0.1wt.%, Al: 0.6wt.%, Ti: 0.14wt.%, Zr: 0.1wt.%, B: 0.99wt.%, Fe as the balance, the main phase alloy raw materials were weighed, and smelted in a vacuum induction melting furnace under the protection of Ar gas atmosphere, and the molten liquid was cast onto a water-cooled copper roller with a rotation speed of 32rpm. The liquid casting temperature was 1400°C, and the main phase alloy flakes with an average thickness of 0.27mm were obtained;
[0116] (2) According to the designed composition ratio of 100 mass % PrNd: 19.3wt.%, Ce: 13.7wt.%, Dy: 0.4wt.%, Co: 1.3wt.%, Cu: 0.1wt.%, Ga: 0.1wt.%, Al: 0.35wt.%, Ti: 0.1wt.%, Zr: 0.1wt.%, B: 0.99wt.%, Fe balance, weigh the auxiliary phase alloy raw materials, use a vacuum induction melting furnace to melt under the protection of Ar gas atmosphere, and cast the molten liquid onto a water-cooled copper roller with a rotation speed of 36rpm. The liquid casting temperature is 1400°C, and the auxiliary phase alloy flakes with an average thickness of 0.25mm are obtained;
[0117] (3) The main phase alloy flakes and the auxiliary phase alloy flakes are respectively subjected to hydrogen crushing, dehydrogenation, and air flow grinding to form alloy powders with an average particle size of 5 μm and 3.5 μm, and mixed at a mass ratio of 2.7:1 under the protection of N2 atmosphere, and tributyl borate as a lubricant is added in an amount of 0.05 wt% of the alloy powder, and stirred to mix evenly;
[0118] (4) The mixed powder was filled into the mold cavity of the pressing equipment under the protection of N2 atmosphere, and the oriented magnetic field strength was 3T for orientation molding and pressing, and then the isostatic pressing was carried out at a pressure of 185 MPa for 8 seconds in an isostatic press to obtain a density of 4.2 g / cm 3 of compact;
[0119] (5) The green body is placed in a sintering furnace and subjected to a heating treatment in a vacuum atmosphere. The green body is kept at 150°C and 260°C for 100 min respectively for lubricant removal treatment, and kept at 600°C and 900°C for 90 min respectively for degassing treatment. Then, a 4-stage sintering and heat-keeping process is performed. After each sintering and heat-keeping stage, the temperature is first lowered to 990°C and then raised to the next heating step. The specific sintering process is shown in Table 2. After the fourth stage of sintering and heat-keeping, the green body is directly cooled to room temperature to obtain a sintered body.
[0120] (6) Aging treatment: Take the above sintered body, heat it to 900°C and keep it for 180 minutes, then cool it to 200°C, then heat it to 530°C and keep it for 240 minutes, and then cool it to room temperature to obtain a magnet after aging treatment. The NdCeFeB permanent magnet has the following chemical formula: (Ce 0.11 RH 0.01 RL 0.88 ) 33.1 Fe 63.56 TM 2.35 B 0.99 ;
[0121] The RH elements are Dy, the RL elements are Pr and Nd; and the TM elements are Co, Cu, Ga, Al, Zr and Ti.
[0122] Comparative Example 6
[0123] The difference between Comparative Example 6 and Example 4 is that Comparative Example 6 adopts a 3-stage sintering and heat preservation process. The specific sintering process is shown in Table 2.
[0124] Example 5
[0125] The only difference between Example 5 and Example 4 is the powder making step (3). In Example 5, the main phase alloy flakes and the auxiliary phase alloy flakes are mixed in a mass ratio of 2.7:1, and then hydrogen crushed, dehydrogenated, and air flow ground into an alloy powder with an average particle size of 3.7 μm. Under the protection of N2 atmosphere, a lubricant tributyl borate accounting for 0.05 wt% of the alloy powder is added, and the mixture is stirred and mixed evenly.
[0126] Comparative Example 7
[0127] The difference between Comparative Example 7 and Example 5 is that Comparative Example 7 adopts a 3-stage sintering and heat preservation process. The specific sintering process is shown in Table 2.
[0128] Table 2: Process parameters of heating and sintering of Examples 4-5 and Comparative Examples 6-7
[0129]
[0130]
[0131] Table 2 (Continued) Process parameters of heating and sintering of Examples 4-5 and Comparative Examples 6-7
[0132]
[0133] The magnets after aging treatment in each of Examples 1-5 and Comparative Examples 1-7 were processed to standard Sample column, using BH instrument to test the magnetic performance, specific magnetic performance test results.
[0134] The magnetic properties of the magnets prepared in the above-mentioned Examples 1-5 and Comparative Examples 1-7 were tested respectively by the NIM-62000 permanent magnet material precision measurement system; the area percentage was analyzed by using the Image-Pro Plus software, and the results are shown in Table 3 below;
[0135] Among them, the area ratio of the RE-rich phase to the entire field of view is recorded as area ratio S1;
[0136] The average value of the ratio of the sum of the areas of the agglomerated grain boundary RE-rich phase located at the intersection of three or more main phase grains to the sum of the total areas of all three or more adjacent main phase grains is S2.
[0137] The average grain size is the average grain size of the main phase grains.
[0138] Table 3 Product performance of Examples 1-5 and Comparative Examples 1-7
[0139]
[0140]
[0141] In Table 3, “-” means not detected.
[0142] By comparing Example 1 with Comparative Example 1, it can be seen that the 4-stage sintering and heat preservation process effectively reduces the area ratio of the agglomerated grain boundary RE-rich phase, makes the grain boundary RE-rich phase finer, and significantly improves the magnetic properties of the magnet.
[0143] Comparing Example 1 with Example 2 and Comparative Example 2, it can be seen that the 5-stage sintering and heat preservation process can further improve the magnet performance, but the improvement effect is limited. However, the 4-stage sintering and heat preservation process has a significantly better improvement effect on performance (see Example 1) than the 3-stage sintering and heat preservation process (see Comparative Example 2).
[0144] The improvement in magnetic properties, S1, and S2 between Example 1 and Comparative Example 2 is significantly better than that between Comparative Example 3 and Comparative Example 4, indicating that the performance improvement effect of the high Ce content magnet using the 4-stage sintering and insulation process is significantly better than that of the low Ce content magnet.
[0145] By comparing Example 3 with Comparative Example 5, it can be seen that the four-stage sintering and heat-insulating process can optimize the grain boundary phase distribution, thereby significantly improving the diffusion effect of the magnet.
[0146] By comparing Example 4 with Comparative Example 6, and Example 5 with Comparative Example 7, it can be seen that the magnetic properties of the dual alloy magnet using the 4-stage sintering and heat-insulating process are also better than those using the 3-stage sintering and heat-insulating process.
[0147] The above is an explanation of the embodiments of the present invention. However, the present invention is not limited to the above embodiments. Any modification, equivalent replacement, improvement, etc. made within the spirit and principle of the present invention shall be included in the protection scope of the present invention.
Claims
1. A Nd:Ce:Fe:B permanent magnet, characterized in that: The NdCeFeB permanent magnet has at least one of the following characteristics: The area of RE-rich phase at the grain boundaries in the magnet accounts for more than 6% of the entire field of view; The RE-rich phase at the grain boundaries in the magnet is evenly and finely distributed; The average ratio of the area of the agglomerated grain boundary RE-rich phase located at the intersection of three or more main phase grains to the total area of all three or more adjacent main phase grains is ≤15%; The NdCeFeB permanent magnet has the following chemical formula: a RH b RL 1-a-b ) x Fe 100-x-y-z TM y B z ; Wherein: 20≤x≤40, 0.5≤y≤10, 0.9≤z≤1.5, 0.05≤a≤0.65, 0.01≤b≤0.25; RH element is at least one of Dy, Tb, Ho, Gd, RL element is at least one of Pr, Nd, La, Y, and contains at least Nd; TM element is at least one of Co, Cu, Ga, Al, Zr and Ti; The method for preparing the NdCeFeB permanent magnet comprises: powdering, pressing, sintering and aging the raw materials including Ce element, RL element, Fe element, TM element, B element and RH element to prepare the NdCeFeB permanent magnet; The sintering is vacuum liquid phase sintering, which has more than four sintering and heat preservation stages, the temperature of the sintering and heat preservation stages is 900-1150° C., and the heat preservation temperatures of multiple heat preservation stages are the same or different; the heat preservation time is 40-140 minutes; Between each two adjacent sintering and heat preservation processes, the next heating and heat preservation process is directly carried out after the previous sintering and heat preservation stage is completed, or after the previous sintering and heat preservation stage is completed, cooling is first carried out, and then the next heating and heat preservation process is carried out; After the insulation is completed, the cooling temperature is 500-1050℃.
2. The Nd:Ce:Fe:B permanent magnet according to claim 1, characterized in that: The RE includes neodymium and at least one selected from the group consisting of the following rare earth elements: cerium, lanthanum, praseodymium, yttrium, gadolinium, terbium, dysprosium, and holmium.
3. The Nd:Ce:Fe:B permanent magnet according to claim 1, characterized in that: The main phase has R2Fe 14 B structure; The average grain size of the main phase grains of the NdCeFeB permanent magnet is 5-10 μm.
4. The Nd:Ce:Fe:B permanent magnet according to claim 1, characterized in that: 25≤x≤35, 1≤y≤5, 0.9≤z≤1.3, 0.05≤a≤0.25, 0.01≤b≤0.
1.
5. The Nd:Ce:Fe:B permanent magnet according to claim 1, characterized in that: A lubricant is also added in the method, and the lubricant is selected from one or more of calcium stearate, zinc stearate, tributyl borate, isopropyl alcohol and petroleum ether.
6. The Nd:Ce:Fe:B permanent magnet according to claim 5, characterized in that: The amount of the lubricant used is 0.01-2wt% of the total weight of the powder.
7. The Nd:Ce:Fe:B permanent magnet according to claim 1, characterized in that: The method further comprises: (K1) firstly preparing Ce-free main phase alloy flakes and Ce-containing auxiliary phase alloy flakes respectively; The Ce-free main phase alloy flakes are prepared by melting and condensing raw materials of RL elements, Fe elements, TM elements, B elements, and optionally RH elements to form alloy flakes; The Ce-containing auxiliary phase alloy flakes are prepared by smelting and condensing raw materials of Ce element, RL element, Fe element, TM element and B element, and optionally existing or not existing RH element; (K2) The Ce-free main phase alloy flakes and Ce-containing auxiliary phase alloy flakes in step (K1) are respectively subjected to hydrogen crushing, dehydrogenation, and air flow grinding to form alloy powders; a lubricant is optionally added, and the powders are pressed, sintered, and aged to prepare the Nd:Ce:Fe:B permanent magnets.
8. The Nd:Ce:Fe:B permanent magnet according to claim 7, characterized in that: The method further comprises: (S1) first preparing Ce-free main phase alloy flakes and Ce-containing auxiliary phase alloy flakes respectively, and respectively preparing main phase alloy powder and auxiliary phase alloy powder by hydrogen crushing, dehydrogenation and air flow grinding; The Ce-free main phase alloy flakes and Ce-containing auxiliary phase alloy flakes have the above meanings; (S2) mixing the main phase alloy powder and the auxiliary phase alloy powder in step (S1), optionally adding or not adding a lubricant, pressing, sintering, and aging treatment to prepare the Nd:Ce:Fe:B permanent magnet.
9. The Nd:Ce:Fe:B permanent magnet according to claim 8, characterized in that: In step (S2), the main phase alloy powder and the auxiliary phase alloy powder in step (S1) are mixed, a lubricant is added, and the mixture is pressed, sintered, and aged to prepare the Nd:Ce:Fe:B permanent magnet.
10. The Nd:Ce:Fe:B permanent magnet according to claim 8, characterized in that: In step (S2), the mass ratio of the main phase alloy powder to the auxiliary phase alloy powder is (1-40):
1.
11. The Nd:Ce:Fe:B permanent magnet according to claim 7, characterized in that: The preparation method further comprises pressing the alloy powder into a compact.
12. The Nd:Ce:Fe:B permanent magnet according to claim 11, characterized in that: The press molding includes orientation press molding and isostatic press molding.
13. The Nd:Ce:Fe:B permanent magnet according to claim 12, characterized in that: The magnetic field strength of the orientation magnetic field is 2-5T.
14. The Nd:Ce:Fe:B permanent magnet according to claim 12, characterized in that: The isostatic pressing pressure is 150-260 MPa.
15. The Nd:Ce:Fe:B permanent magnet according to claim 11, characterized in that: The density of the compact is 4-6 g / cm 3 .
16. The Nd:Ce:Fe:B permanent magnet according to claim 1, characterized in that: The sintering is vacuum liquid phase sintering, which has 4 to 10 sintering and heat preservation stages.
17. The Nd:Ce:Fe:B permanent magnet according to claim 1, characterized in that: The sintering and heat preservation stage includes a heating stage before the sintering and heat preservation stage, and the heating rate of the heating stage is 0.5-5°C / min.
18. The Nd:Ce:Fe:B permanent magnet according to claim 1, characterized in that: After the first sintering and heat preservation stage is completed, the first 1-10 stages of cooling are carried out, and then the next step of heating and heat preservation process is carried out.
19. The Nd:Ce:Fe:B permanent magnet according to claim 1, characterized in that: The aging treatment is performed after the sintering treatment is cooled.
20. The Nd:Ce:Fe:B permanent magnet according to claim 19, characterized in that: The aging treatment is a secondary aging treatment, including: heating for a first aging treatment, the first aging treatment temperature is 800-950°C, and the heat preservation time is 160-300min; cooling to below 210°C, and then heating for a second aging treatment, the second aging treatment temperature is between 450-600°C, and the heat preservation time is 240-360min.
21. The Nd:Ce:Fe:B permanent magnet according to claim 1, characterized in that: The method also includes a grain boundary diffusion treatment step, wherein the surface of the NdCeFeB permanent magnet prepared after sintering is ground, coated with a heavy rare earth diffusion source, and subjected to diffusion treatment to prepare a grain boundary diffused NdCeFeB permanent magnet.
22. Application of the Nd:Ce:Fe:B permanent magnet according to any one of claims 1 to 21 in the fields of rare earth permanent magnet motors, smart consumer electronic products, and medical devices.
Citation Information
Patent Citations
R-T-B based sintered magnet
CN106057391A
A Ce-containing rare earth permanent magnet and a preparation method thereof
CN109256250A
Permanent magnet and rotary machine
CN110537232A